Assessment of patient’s knowledge and opinion on organ donation and transplantation in a Brazilian Health Center - Gonçalves, Thiago Barbosa; Teixeira, Renan Kleber Costa; Hosoume, Victor Seiji Nascimento; Silva, José Antonio Cordero da (Brazilian Journal of Transplantation, 2011)
Purpose: To assess the knowledge and opinion of patients in a Brazilian Health Center in Belém on organ donation and transplantation. Method: This is an observational cross-sectional study. It was administered a standardized questionnaire to patients enrolled in the Health Center. It contained questions about the organs donation and transplantation and socio-demographic data. Results: It was interviewed 136 people being most of respondents female with mean age 39, unmarried, with elementary school, and Catholics. Most of respondents were in favor of the organ donation. A slightly smaller amount of respondents would donate their organs; from that group, few people reported their opinion to their families. Most of the sampling believes there is trading of organs in Brazil, and rich people are more likely to receive an organ. Respondents have a low level of awareness on the organs which can be transplanted in humans. Younger people are more likely to donate organs, and most women who are usually responsible by the decision of donating organs of relatives would not allow the transplant. Conclusion: Although the majority of people asserts to be supportive to the organs donation, few potential donors become actual donors, due to people ignoring things on the organ donation and transplantation and the fact that most of people do not inform their family on their willingness to donate organs.